Inoculation of microball granular sludge under aerobic conditions - Pan, Shun (2008)
The objectives of this project are: Firstly, to study the feasibility of development of aerobic granules under aerobic reaction conditions. Secondly, to test the effect of OLR on the aerobic granulation. Thirdly, to investigate the effect of operational parameters, like hydraulic retention time (HRT) and mean cell residence time (MCRT), on the aerobic granulation.